Evaluation of body growth and reproductive development in Brahman and Simbrah F1 stabled heifers - Guillén-Alvarado, María Carolina (2023)
Reproduction is the base of all production systems; therefore, the development of heifer replacements must be a priority for every cattle breeder. This study evaluated the body growth and reproductive aspects of Brahman and Simbrah F1 heifers. Animals were kept under the same environment, handling, and feeding conditions. A total of 60 heifers (30 Brahman and 30 Simbrah F1) were used. During the experiment, the animals were weighed monthly. Also, from 12 to 19 months of age, transrectal ultrasound evaluations were performed to assess the development of the reproductive tract. The variables evaluated in the study were: body weight (BW), body condition score (BCS), diameter of the cervix (DC), diameter of the right uterine horn (DRH), diameter of the left ovary (DLO), diameter of the right ovary (DRO), quantity and size of follicles [TF1 (≥ 10 mm), TF2 (6-9 mm), TF3 (≤ 5 mm)], diameter of the net corpus luteum (DNCL) and cyclicity. Better body weight was obtained for the Simbrah F1 heifers (p=0.0026) compared to Brahman, they were, on average, 50 kg heavier. The CC increased as well as weight (p=0.021) and age (p=0.0485). Regarding reproductive aspects, greater values were obtained for all the variables (DC, DRH, DRO, DLO, TF1, TF2, TF3, and DNCL) in both racial groups as heifers were getting old. In addition, in the Simbrah F1 racial group, the DC (p=0.028), DCD (p=0.0037), and DCLN (p=0.0303) were greater than Brahman; while for DOD, DOI, TF1, TF2, and TF3 the response between the racial groups was similar (p>0.05). This study evidenced a better performance in weight gain and development of reproductive structures of the Simbrah F1 breed group than purebred Brahman heifers.